The impact of cultural values on the electric vehicle purchase intention: Testing the moderating role of subjective norms - Phu Hoang Nguyen; Huong Thu Duong; Sinh Duc Hoang (Innovative Marketing)
Type of the article: Research Article AbstractElectric vehicles are widely considered an environmentally-friendly alternative to conventional vehicles, which contribute to mitigating air pollution and energy consumption. This research is conducted to investigate the impact of cultural values on the electric vehicle purchase intention, as well as testing the moderating role of subjective norms in the influence of both attitude towards electric vehicles and perceived behavioral control on the electric vehicle purchase intention. Using the theory of planned behavior as the theoretical framework, this study collects the data from 394 Vietnamese millennials through a convenience sampling survey. The results from this research indicate that cultural values, including man-nature orientation, collectivism, and long-term orientation positively influence the theory of planned behavior’s factors, which are attitude towards electric vehicles, subjective norms, and perceived behavioral control. Then, three factors in the theory of planned behavior have a positive effect on the electric vehicle purchase intention. Additionally, it is found that subjective norms positively moderate the effect of both attitude towards electric vehicles and perceived behavioral control on the electric vehicle purchase intention. The results from this study contribute to the theory of planned behavior by integrating cultural values and give useful insights for policymakers and marketers in Vietnam to conduct relevant strategies that can enhance electric vehicle adoption. AcknowledgmentThe conduct of this study was supported by the School of Business, International University, Vietnam National University, Ho Chi Minh City.